An Evaluation of Occupational Health and Safety (OHS) Implementation by the HSE Team on Construction Workers' Safety Perception and Work Motivation: - Mubarroq, Ahmad Yudi; Ichwanto, Muhammad Aris; Effendi, Ahmad Naufal; Anindya, Dea Nisfuha; Putra, Fanny Alvido Cahya (ASTONJADRO, 2026)
Occupational Health and Safety (OHS) is a crucial aspect in the construction sector, particularly in high-rise building projects that carry high risks of accidents and reduced worker motivation. This study aims to evaluate the implementation of OHS by the Health, Safety, and Environment (HSE) team on workers’ safety perception and work motivation, with a case study on the BRI Building Project in Semarang conducted by PT. PP (Persero) Tbk. The research employed a quantitative approach with a correlational design and a cross-sectional method. Data were collected through questionnaires distributed to 76 respondents consisting of supervisors, staff, and construction workers. The research instrument was tested for validity and reliability, with a Cronbach’s Alpha value of 0.886, indicating excellent internal consistency. Statistical assumption tests showed that the data were normally distributed; however, the linearity test indicated a significant relationship with deviations from linearity, leading to the use of Spearman’s correlation analysis, with Pearson’s correlation used as a comparison. The analysis results revealed a very strong, negative, and significant relationship between the role of HSE and work motivation (Spearman: r = -0.991; Pearson: r = -0.999; p < 0.01). These findings suggest that strengthening the role of HSE does not always directly increase worker motivation, as it is influenced by non-technical factors such as communication, safety culture, and trust in management. This study provides theoretical contributions by enriching the discussion of HSE’s non-technical roles in fostering safety culture, as well as practical contributions for contractors in designing more comprehensive OHS management strategies.